Digital Game-Based Learning as a Strategy to Expand Vocational Students’ Vocabulary: A Mixed Methods Approach - Abidah, Lailatul; Asih, Ria Arista; Estu Widodo (Journal of Education Technology, 2023)
The Digital Game-Based Learning (DGBL) strategy is widely recommended for digital-native learners to enrich their vocabulary. The purposes of this study was to evaluate the effectiveness of DGBL in expanding students’ vocabulary knowledge. A mixed methods approach was implemented. The quasi-experimental design involved an experimental group (taught with DGBL, N = 29) and a control group (trained with conventional vocabulary learning, N = 28). Each group was assigned a test before and following the intervention, consisting of 30 similar questions. IBM SPSS Statistics 26.0 has been employed to gauge the data collected, and utilized a paired sample t-test in conjunction with an independent sample t-test. The inspection exposed that, using DGBL affects students’ vocabulary learning development. The experimental group’s average score rose from 44.83 to 63.45. However, there was no discernible distinction between the two groups’ mean post-test results. The researchers analyzed three factors causing the insignificant results of the independent sample t-test: time constraints, poor internet connection, and both groups obtaining intentional vocabulary learning. Eight questions in the interview session were asked to the experimental group to explore their views about the DGBL and confirmed the unclear information that resulted in quantitative data. Interviewees agreed that DGBL can enrich vocabulary, increase learning motivation, and reduce boredom.